2020
DOI: 10.1007/s11136-020-02602-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and distress assessed with self and external assessment screening tools in patients with hematologic malignancies attending treatment in an acute hospital

Abstract: Purpose In this study, we examined distress levels and quality of life (QoL) of patients with hematologic malignancies under treatment in an acute setting. We used external- and self-assessment instruments for distress. Additionally, we investigated the relation between distress and QoL as well as whether highly distressed patients differed from less distressed patients concerning their QoL. Methods A cross-sectional study with patients of the Medical Clinic II of the University Hospital Frankfurt was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
4
1
Order By: Relevance
“…In contrast, patients with MM in our study have average Functional Assessment of Cancer Therapy QOL scores that are 10 points lower compared to the AML population and do not improve over the course of the illness, which can span over a decade 20 . Compared to other patients with hematologic malignancies, patients with MM have more pronounced QOL impairments across all domains 22,23 . Furthermore, nearly a quarter of patients with MM, regardless of treatment line, suffered from clinically significant depression, anxiety, or PTSD symptoms.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In contrast, patients with MM in our study have average Functional Assessment of Cancer Therapy QOL scores that are 10 points lower compared to the AML population and do not improve over the course of the illness, which can span over a decade 20 . Compared to other patients with hematologic malignancies, patients with MM have more pronounced QOL impairments across all domains 22,23 . Furthermore, nearly a quarter of patients with MM, regardless of treatment line, suffered from clinically significant depression, anxiety, or PTSD symptoms.…”
Section: Discussioncontrasting
confidence: 60%
“…20 Compared to other patients with hematologic malignancies, patients with MM have more pronounced QOL impairments across all domains. 22,23 Furthermore, nearly a quarter of patients with MM, regardless of treatment line, suffered from clinically significant depression, anxiety, or PTSD symptoms. Although prior studies have shown substantial distress in other patients with hematologic malignancies such as those with AML, the anxiety experienced by AML patients improved significantly with ongoing treatment, whereas distress was reported across the disease continuum in MM.…”
Section: Discussionmentioning
confidence: 99%
“…33 Similar conclusions were reached by other authors who showed that patients with more stress had worse QoL. 32 In our study, patients experienced negative emotions more often during the diagnosis period, likely due to the state of uncertainty about their future and a high level of mental tension. Of course, therapy can also evoke such emotions, but the appropriate support from family, friends and medical staff can reduce their severity.…”
Section: Discussionsupporting
confidence: 90%
“…31 Interestingly, in German observations conducted among 109 patients with HMs, the mean values in both spheres were much lower (37.4 ±37.6 for role functioning and 43.9 ±36.8 for social functioning). 32 It is possible that due to the changes described above, there were significant differences in the emotional domain, assessed in terms of mental tension, worry, irritation, and depression. As shown by the results of a crosssectional study conducted among 87 patients with HMs, a disorder in this sphere of life significantly affects one's global QoL.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also suggest that supplementing item 9 with other screening measures may improve its usefulness in screening for suicide. Using screening instruments that assess population-specific risk factors rather than general ones might help increasing their sensitivity and specificity and simultaneously make them more parsimonious, as a study by Senf et al [19] suggests. This is a factor to be considered when deciding on the optimal screening tool in a certain health care context or for a certain population.…”
Section: Introductionmentioning
confidence: 99%